39. Marriage Mentorship at a Distance - Doxsee, Harry (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2004)
Marriage mentorship is one of the most effective methods through which a couple can enrich their marriage. A good mentorship relationship is based on feelings of warmth and affinity between mentors and mentees. When a relationship of trust is established, the mentees feel more freedom to express their deeper feelings and to explore new paths of mutual understanding. In what ways does the quality of interaction change when mentors and mentees interact via a technological medium such as online audio-conferencing? This paper compares three marriage mentoring experiences that employed online conferencing as the medium of interaction. Audio-conferencing methods provided a particularly warm, trusting interaction between participants, and an effective environment for learning and for practicing communication skills. The paper makes recommendations for efficient online mentoring practice, and builds on a previous discussion of online practice in the community advocacy context (Report #35 in this series).